(untitled) (GIST – Education and Learning Research Journal, 2023)
This study is intended to document Lesson Study experience of six preservice English language teachers studying at a state university in Turkey and investigates its impact on their personal development as prospective language teachers. The large volume of data collected through unstructured interviews, semi-structured interviews, learning journals, classroom observation records and focus group interview during seven-month period was subjected to thematic and categorical analysis using qualitative analysis software. The results revealed that Lesson Study intervention contributed to the personal development of the participating preservice teachers significantly in variety of aspects especially in making critical teaching judgements and ensuring adaptable teaching in the classroom. The results further indicated that Lesson Study also led to the development in creative teaching, establishment of rapport with students, self-awareness, and self-confidence of the participants.